InP/InGaAsP multiple quantum well multimode interference coupler - Shim, SI; Kim, KT; Kim, KM; Kim, HD; Kim, SE; Park, JH; Woo, DH (KOREAN PHYSICAL SOC, 2001)
An optical coupler was designed and fabricated based on multimode interference (MMI) within the InP/InGaAsP Multiple Quantum Well (MQW) structure for use at the 1.55-mum wavelength. A theoretical analysis of MMI is presented by using the beam propagation method (BPM). The MMI section was designed to be a rib-type waveguide by using the effective refractive index method. A 2 x 2 optical coupler, which has a rib-type waveguide for the MMI section, was fabricated and tested. It showed a good self-imaging property, which is the characteristic of the MMI effect.
Keywords: REFRACTIVE-INDEX; INP